Methods of corn breeding - Schafer, Edwin George (My University, 1907)
Introduction: Our common corn belongs to the tribe Mayadae, and is known botanically as Zea Mays. It has never been found in its wild state, but is generally beleived to be a native of tropical America. It was cultivated by the Indians at the time of America's discovery. Since that time it has been one of the most largely grown of all cereals. The crop of the United States alone being nearly 100,000,000 acres, the average yield being about twenty-five bushels per acre. Fifty to sixty bushels per acre is a very common yield, while seventy-five to one hundred bushels is often obtained. This shows us that some yield must be exceedingly low, and if improvement cannot be made on a part of this acreage, it should be used for other purposes. The value of this great product or cereal is based upon the quantity and quality of grain produced. Anything that will materially increase either one without suffering a decrease in the other will be of great economic importance. Our object should be to secure the largest yields of corn of a high feeding value, at a relatively small cost. As has been shown, there is a large difference in yields per acre, which indicates that some conditions for growing the crop must be much more favorable than others. These conditions are governed by soil, climate, culture and seed, and whenever practical better conditions should be secured and better methods adopted.
Citation: Schafer, Edwin George. Methods of corn breeding. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Corn; Corn Breeding; Agricultural Techniques; Theses